Phenolic compounds profile, nutritional compounds and bioactive properties of Lycium barbarum L.: A comparative study with stems and fruits - Pires, Tânia C.S. (2018)
The increasing awareness of the possible health benefits of berry fruits (Lycium barbarum L.) has led to a higher consumption of this type of food products. One of the many examples are the fruits from Lycium genus, traditionally used due to their beneficial properties and health benefits associated with liver, kidney, eyesight, immune system, circulation and longevity disorders. In the present study fruits and stems of Lycium barbarum L. (goji) were characterized in terms of nutritional profile, sugars, organic acids, fatty acids and tocopherols. Furthermore, a phenolic characterization of their hydromethanolic extracts was performed and correlated with bioactive properties such as antioxidant, hepatotoxic and antibacterial activities. Stems presented higher values of energy, MUFA (monounsaturated fatty acids), tocopherols and flavonols. Stems also showed greater antioxidant and antibacterial (against Gram-negative bacteria) activities. Otherwise, fruits revealed higher contents of sugars, PUFA (polyunsaturated fatty acids) and hydroxycinnamic acid derivatives, and greater activity against Gram-positive bacteria. This is an innovative study that shows the high potential of goji stems and fruits as sources of bioactive compounds, which could be used in nutraceutical formulations, or incorporated into food products with functional properties. Furthermore, the use of stems could bring industrial sustainability as a valuable by-product, which has been scarcely reported.